Alison Porter in Look Back in Anger: Is She Responsible for her Sufferings? - Haque, Salma (IIUC Studies, 2016)
John Osbornes play Look Back in Anger is a dramatic study of a strained marriage relationship. In it Jimmy Porter is the protagonist and Alison Porter, a retired Colonels daughter, is the heroine. The actual action of the play is centered around Jimmys relationship with her. Despite his dominance, his wife Alison Porter, is the most important supporting character on whom Jimmy inflicts pain by his tirades all the time until eventually she feels she can bear no more. Later on she leaves him in her pregnant state to seek peace. After the loss of the baby she comes back to him when both have lost faith in each other. So they will go back to their previous unhealthy relationship causing her to become deplorable again. My reading of Alison Porter is that she is a suffering person though some find Jimmy a sufferer. This paper aims at assessing her sufferings and the reasons behind them. IIUC Studies Vol.10 & 11 December 2014: 65-80